A messy trajectory: From medical sociology to crip theory - Egner J. (Research in Social Science and Disability ; 9, 2016)
Purpose The purpose of this paper is to draw attention to the work of sociologists who laid the foundation for queer and crip approaches to disability and to address how queer and crip theory has and can help to re-conceptualize our understandings of health, illness, disability, and sexuality. Methodology/approach This paper is an examination of historical moments and prominent literature within medical sociology and sociology of disability. Sociological and popular understandings of disability and sexuality have often mirrored each other historically. Although this literature review focuses primarily on medical sociology and disability studies literature, some works of scholars specializing in gender studies, sexuality, literature, history, and queer studies are also included Findings In this paper, I argue that the medicalization and pathologization of human differences specifically as it pertains to sexuality and disability within the medical sociological literature have led to constructionist, social model, and feminist critiques. It is these critiques that then laid the foundation for the development of queer and crip theoretical approaches to both disability and sexuality. Originality/value Crip and queer approaches to disability provide a clear call for future sociological research. Few social science scholars have applied queer and crip approaches in empirical studies on disability. The majority of work in this area is located in the humanities and concerned with literary criticism. A broader array of empirical work on the intersection of sexuality and disability from queer/crip perspectives is needed both to refine these postmodern theoretical models and to examine their implications for the complex lived experience that lies at the intersection of sexuality and disability. In queering disability and cripping sexuality and gender, we may be able not only to more fully conceptualize disability, sexuality, and gender as individual social categories, but also to more fully understand the complex intersection of these social locations.
Keywords: EDI; approches et analyses; care; cours; crip; discipline; histoire et politique; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sociologie; sofia; thématiques

Transidentités: ordre & panique de genre : le réel et ses interprétations - Espineira, Karine; Bertini, Marie-Joseph (Collection Logiques sociales. Série Sociologie du genre, 2015)
Engagée dans une recherche sur le terrain transidentitaire, la chercheuse s'attache à croiser état des lieux du terrain associatif et militant trans avec l'histoire des définitions de la médecine légale, mettant à jour la politisation des groupes, les apports des nouveaux médias et les effets de la médiatisation sur les personnes transgenres. Cet ouvrage est complémentaire du titre Médiacultures: la transidentité en télévision, édité simultanément.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; histoire et politique; militance; premier cycle; périodes historiques; queer; régions géographiques; santé; sciences humaines; soc2014; sociologie; thématiques; transféminisme

La contestation des politiques de changement d’identité de genre par les militantes et militants trans québécois - Enriquez, Mickael Chacha (Lien social et Politiques, 2013)
Les politiques de changement de genre sont fortement critiquées par les militants et militantes trans (transsexuels, transgenres, etc.) qui non seulement les dénoncent, mais mettent en place plusieurs stratégies de résistance afin d’améliorer leur accès aux processus de transition. Basé sur une recherche qualitative menée auprès de 12 activistes trans au Québec, cet article rend compte de leur perception des politiques québécoises de changement de genre. Il met en évidence le cadre transphobe et cisnormatif au sein duquel se mettent en place ces politiques, et permet de comprendre dans quelle mesure les stratégies de résistance mises en place s’adaptent à ce cadre ou le contestent
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; histoire et politique; pol4212; premier cycle; périodes historiques; queer; québec; régions géographiques; sciences humaines; sociologie; thématiques; trans; transféminisme; transidentité; transition de genre

Comprendre le féminisme - Bourcier, Sam (M.H); Moliner, Alice (Max Milo, 2012)
La dichotomie homme/femme n’est pas évidente. Le « nous » féministe est loin d’aller de soi. Sa définition change en fonction des courants et des idéologies. Lutte contre la domination masculine, le féminisme peut aussi défendre les différentes expressions de genres et de sexualités. En s’interrogeant sur les idées défendues par les différents courants féministes et comment ils s’inscrivent dans le paysage social, l’auteur précise la direction vers laquelle ils doivent s’unir si le féminisme veut rester un mouvement historiquement fécond.
Keywords: 2000 à aujourd'hui; approches et analyses; cours; discipline; europe; fem1000; france; har4600; histoire et politique; intersectionnalité; mouvements féministes; patriarcat; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques

Émergence et activités de l’organisation internationale des intersexué·e·s - Guillot, Vincent (Nouvelles Questions Feministes, 2008)
Keywords: 1900-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; corps; cours; discipline; europe; histoire et politique; hétérosexisme; identités LGBTQIA2+; militance; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Femmes, genre, féminisme - Trat, Josette (Les cahiers de "Critique communiste", 2007)
"Le retour sur l'histoire du courant féministe "lutte de classes" met en évidence l'urgence à penser les rapports sociaux de sexe en les articulant aux rapports de classe et aux rapports Nord-Sud. Quels sont les apports et les limites du Queer pour penser le genre et les oppressions? Quels sont les rapports entre les mouvements féministes et les mouvements gais et lesbiens? Quels sont les effets de la mondialisation néolibérale sur l'oppression des femmes et sur leurs luttes à l'échelle mondiale? Les questions des rapports de classe et celle du racisme ont été également remises au-devant de la scène par la révolte des banlieues dont les filles semblaient toutefois singulièrement absentes. Pourtant, elles luttent contre le sexisme, ainsi que le montre le collectif Féminin-Masculin de Vitry. A l'heure où les retours en arrière sont toujours possibles, comme en atteste l'émergence d'un mouvement masculiniste, la construction d'un courant féministe se donnant pour objectif de changer radicalement la société reste nécessaire pour gagner l'égalité réelle entre hommes et femmes."
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; histoire et politique; intersectionnalité; militance; premier cycle; queer; rapports de classe; rapports sociaux de sexe; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques

Aberrations in Black: Toward a queer of color critique - Ferguson, Roderick A. (Critical American studies series, 2004)
A hard-hitting look at the regulation of sexual difference and its role in circumscribing African American culture. The sociology of race relations in America typically describes an intersection of poverty, race, and economic discrimination. But what is missing from the picture—sexual difference—can be as instructive as what is present. In this ambitious work, Roderick A. Ferguson reveals how the discourses of sexuality are used to articulate theories of racial difference in the field of sociology.
Keywords: amériques; approches et analyses; cours; discipline; discours dominant; fem1000; fem3300; histoire et politique; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; queer of color; racisme; ressource en ligne; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; violences; états-unis

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

The rise of a gay and lesbian movement - Adam, Barry D. (Social movements past and present, 1987)
The past decade has seen a wealth of changes in the gay and lesbian movement and a remarkable growth in gay and lesbian studies. In response to this heightened activity Barry D. Adam has updated his 1987 study of the movement to offer a critical reflection on strategies and objectives that have been developed for the protection and welfare of those who love others of their own sex. This revised volume addresses the movement's recovery of momentum in the wake of New Right campaigns and its gains in human rights and domestic partners' legislation in several countries; the impact of AIDS on movement issues and strategies and the renewal of militant tactics through AIDS activism and Queer Nation; internal debates that continually shift the meanings composing homosexual, gay, lesbian, and queer identities and cultures; the proliferation of new movement groups in Eastern Europe, Latin America, Asia, and Africa; and new developments in historical scholarship that are enriching our understanding of same-sex bonding in the past. Adam delineates the formation of gay and lesbian movements as truly a world phenomenon, exploring their histories in the United States, Great Britain, Germany, France, Canada, Scandinavia, Australia, and countries for which very little information about the activities of gay men and lesbians has been made available. In this global picture of the mobilization of homosexuals Adam identifies the critical factors that have given personal and historical subjectivity to desire, that have shaped the faces and territories of homosexual people, and that have generated homophobia and heterosexism. Treating the sociological aspects of the rise of the gay and lesbian movement, Adamalso looks at "new social movements" theory in relation to the gay and lesbian movement and cultural nationalism - whether in the form of cultural feminism or queer nationalism - which he considers an important, perhaps inevitable, moment in the empowerment of inferiorized people.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; activisme; afrique; allemagne; amériques; approches et analyses; asie; canada; cours; discipline; europe; europe de l'est; france; histoire; histoire et politique; homophobie; hétérosexisme; identité sexuelle; identités LGBTQIA2+; justice sociale; militance; mobilisation; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; premier cycle; périodes historiques; queer; royaume-uni; régions géographiques; scandinavie; sciences humaines; sex1183; sociologie; systèmes d'oppressions; thématiques; états-unis